Sensitivity of Older Patients to Antipsychotic Motor Side Effects: A PET Study Examining Potential Mechanisms - Uchida, Hiroyuki; Kapur, Shitij; Mulsant, Benoit H.; Graff-Guerrero, Ariel; Pollock, Bruce G.; Mamo, David C. (The American journal of geriatric psychiatry, 2009)
It is generally held that the elderly are more sensitive to motor side effects of antipsychotics, although the mechanisms for such an effect are not fully understood. The objective of this study was to examine whether this sensitivity is due to a central pharmacokinetic (i.e., higher occupancy for a given plasma level) or pharmacodynamic (i.e., greater functional effects for a given occupancy) effect. Crosssectional. Centre for Addiction and Mental Health, Toronto, Ontario, Canada. Thirteen subjects aged 50 (mean ± standard deviation age: 62 ± 9 years) with schizophrenia or schizoaffective disorder who were receiving risperidone. Dopamine D2 binding potential in the striatum, using [11C]raclopride positron emission tomography scan. D2 receptor occupancy was calculated, using age-corrected measure from healthy individuals and region of interest analysis. The authors observed the expected nonlinear relationship between total risperidone and 9-hydroxyrisperidone plasma level and striatal D2 receptor occupancy. The estimated plasma level of risperidone plus 9-hydroxyrisperidone associated with 50% maximal receptor occupancy was 7.3 ng/mL, which is similar to what has been reported in younger patients. However, extrapyramidal side effects (EPS) were observed in seven subjects at D2 occupancy of 34%–79%, occupancy levels that are lower than previously reported for younger patients in whom EPS are rare at occupancies lower than 80%. The observation of greater functional effect (EPS in this case) for a given drug occupancy than the younger patients supports a pharmacodynamic mechanism for age-related antipsychotic drug sensitivity. This finding has important implications for dosing of antipsychotics in older patients with schizophrenia.